2003
DOI: 10.1103/physrevb.68.115101
|View full text |Cite
|
Sign up to set email alerts
|

Theory of orbital moment collapse under pressure inFeI2

Abstract: FeI 2 is an insulating antiferromagnet with an unusual magnetic structure at ambient pressure. Recently, hyperfine field, electric field gradient, and other local quantities at the Fe site were measured over a wide range of pressures indicating a collapse of the orbital magnetic moment below the insulator-to-metal transition. In the present work we apply local density approximation ͑LDA͒ and LDAϩU approaches to calculate the electronic structure and to investigate the Fe on-site quantities. We propose that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…A different orbital occupation would lead to different orbital and dipolar hyperfine fields. This has not been examined any further in the present work, but it has been shown before that LDA + U can stabilize qualitatively different orbital occupations in iron compounds [131] and in lanthanide [121] compounds.…”
Section: Hyperfine Propertiesmentioning
confidence: 74%
“…A different orbital occupation would lead to different orbital and dipolar hyperfine fields. This has not been examined any further in the present work, but it has been shown before that LDA + U can stabilize qualitatively different orbital occupations in iron compounds [131] and in lanthanide [121] compounds.…”
Section: Hyperfine Propertiesmentioning
confidence: 74%
“…IP transition and the quenching of the orbital term take place at the same pressure range with no volume nor isomer shift (IS) change 3 [34] gives rather strong evidence that the observed lattice distortion in the c-direction, at the IP phase, is indeed attributed to the quenching of the orbital term. It is worth mentioning that Kunes et al [35], based on electronic structure calculations for FeI 2 , concluded that the quenching of the orbital term originates from a pressure-induced change of the sym-metry of the occupied minority-spin d-d orbital; namely, a change from a twofold-degenerate e 0 g orbital to a g occupation. The latter orbital is characterized by a very strong anisotropy of the charge and spin distribution, with the angular part stretched along the hexagonal c axis.…”
Section: A Case Of a Mott Transition Driven By An Increasing Crystal-mentioning
confidence: 99%
“…Since for U ¼ 0:5 and 0.6 Ry two different solutions were obtained and because it is possible to obtain many different solutions with LSDA þ U method depending on the initial density matrices, it seems appropriate to mention that the LSDA þ U total energies do not necessarily provide unambiguous criterion for the true ground state [9,38,39].…”
Section: Lsda-soc Calculationsmentioning
confidence: 99%